2003
DOI: 10.1146/annurev.psych.54.101601.145128
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Studies of Language Production and Comprehension

Abstract: The 1990s were dubbed the "Decade of the Brain." During this time there was a marked increase in the amount of neuroimaging work observing how the brain accomplishes many tasks, including the processing of language. In this chapter we review the past 15 years of neuroimaging research on language production and comprehension. The findings of these studies indicate that the processing involved in language use occurs in diffuse brain regions. These regions include Broca's and Wernicke's areas, primary auditory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
152
3
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(169 citation statements)
references
References 101 publications
(145 reference statements)
9
152
3
5
Order By: Relevance
“…The activation observed in the right-hemispheric counterpart of Wernicke"s area in the temporal lobe strengthens the hypothesis of Grodzinsky and Friederici (2006), who linked this area to lexical and syntactic information integration. Moreover, the temporal lobe is known to be responsible for processing phonological information, not exclusively, but proven to be vital for perception of language (Gernsbacher and Kaschak, 2003). The dichotic listening task is very clearly a task of phonological perception which requires involvement of the left posterior temporal lobe, which we indeed have found.…”
Section: Discussionsupporting
confidence: 69%
“…The activation observed in the right-hemispheric counterpart of Wernicke"s area in the temporal lobe strengthens the hypothesis of Grodzinsky and Friederici (2006), who linked this area to lexical and syntactic information integration. Moreover, the temporal lobe is known to be responsible for processing phonological information, not exclusively, but proven to be vital for perception of language (Gernsbacher and Kaschak, 2003). The dichotic listening task is very clearly a task of phonological perception which requires involvement of the left posterior temporal lobe, which we indeed have found.…”
Section: Discussionsupporting
confidence: 69%
“…In her review, Bookheimer (2002) explains that the IFG “appears to represent a unique brain region involved not in decoding meaning of individual words but in processing semantic relationships between words or phrases, or in retrieving semantic information”. Semantic processing of visual stimuli and the search for a solution concept of the triads is thus reflected in our data by the activated left‐sided brain network, which is in accordance with previous results (Bookheimer 2002; Gernsbacher and Kaschak 2003; Ilg et al. 2007).…”
Section: Discussionsupporting
confidence: 92%
“…For intuition‐based decisions at the threshold of awareness, we observed a left‐sided brain network of activity within the OFC, the insular cortex, the IFG (extending into the frontal pole), ITG, and the posterior part of the MTG, a network that conforms to previous findings in the language processing literature. In particular, these areas have been discussed in the context of semantic processing of graphematic (visual) stimuli and verbal working memory processes, especially when the search for a solution or a related concept is ensued (Bookheimer 2002; Gernsbacher and Kaschak 2003). Thus the observed network mainly reflects the semantic processing initiated by the three clue words in our task.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is suggested that in Experiment 2 the additional attempt to predict upcoming words involves (parts of) the language production system (Pickering, and Garrod, 2007). Language comprehension and production are associated with activity in the (pre-) frontal cortex, especially when semantic information has to be judged (Bookheimer, 2002;Gernsbacher, and Kaschak, 2003), which may have resulted in a shift of the N400 effects towards anterior electrodes in Experiment 2 as opposed to Experiment 1. Further research is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%